Stock prices and economic activity nexus in OECD countries: New evidence from an asymmetric panel Granger causality test in the frequency domain - Veli Yilanci; Onder Ozgur; Muhammed Sehid Gorus (Financial Innovation, 2021)
This study investigates the stock price-economic activity nexus in 12 member countries of the Organization for Economic Cooperation and Development (OECD) by employing monthly data over the period 1981:1-2018:3. For this purpose, the study uses Granger causality in the frequency domain in the panel setting by decomposing the symmetric and asymmetric fluctuations. This methodology determines whether the predictive power of interested variables is concentrated on quickly, moderately, or slowly fluctuating components. Our findings show that the stock prices have predictive power for future long-term economic activity in the panel setting. However, economic activity has more reliable information for stock prices for negative components. Additionally, empirical findings for asymmetric shocks are not fully consistent with those of symmetric ones. Besides, the country-specific results provide different causal linkages across members and frequencies. These findings may provide valuable information for policymakers to design proper and effective policies in OECD countries regarding the stock market and economic activity nexus.
Keywords: C32; E32; E44; 650; Asymmetric causality; Economic activity; Frequency domain; OECD countries; Panel data; Stock prices